2015
DOI: 10.1080/15384101.2015.1036209
|View full text |Cite|
|
Sign up to set email alerts
|

The evolutionarily conserved transcription factor PRDM12 controls sensory neuron development and pain perception

Abstract: These authors contributed equally to this work.Keywords: Hamlet, nociception, PRDM12, sensory neurons, TRHDE Abbreviation: PRDM12, PR homology domain-containing member 12; HSAN, hereditary and sensory autonomic neuropathy; TRHDE, tyrotropin-releasing hormone degrading enzyme; RA, retinoic acid; Brn3d, brain 3d; Tlx3, T-cell leukemia homeobox 3; Hmx3, H6 family homeobox 3; Drgx, dorsal root ganglia homeobox; Sncg, Synuclein Gamma (Breast Cancer-Specific Protein 1); En1, engrailed-1; RT-qPCR, real-time quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 49 publications
(40 reference statements)
2
54
0
2
Order By: Relevance
“…The encoded protein is an extracellular peptidase that specifically cleaves and inactivates the neuropeptide thyrotropin-releasing hormone (Bauer et al, 1999). Concurring with this, knockdown of TRHDE in Drosophila sensory neurons is known to result in altered cellular morphology, impaired nociception and the sensory response to (potentially) harmful stimuli (Nagy et al, 2015). In our study, carriers of the minor allele showed a slower increase of cerebellum white matter, followed by reduced decline in older age (Supplementary Figure S5).…”
Section: Age-dependent Associations With Brain-structural Change Ratessupporting
confidence: 50%
“…The encoded protein is an extracellular peptidase that specifically cleaves and inactivates the neuropeptide thyrotropin-releasing hormone (Bauer et al, 1999). Concurring with this, knockdown of TRHDE in Drosophila sensory neurons is known to result in altered cellular morphology, impaired nociception and the sensory response to (potentially) harmful stimuli (Nagy et al, 2015). In our study, carriers of the minor allele showed a slower increase of cerebellum white matter, followed by reduced decline in older age (Supplementary Figure S5).…”
Section: Age-dependent Associations With Brain-structural Change Ratessupporting
confidence: 50%
“…By contrast, our data indicate that Xenopus or mouse Prdm12 promotes En1 + V1 INs when overexpressed in the frog or chick embryo. Human PRDM12 also induces en1 when overexpressed in the frog (Nagy et al, 2015). The reasons for this functional difference between zebrafish and tetrapode vertebrate Prdm12 are unclear and remain to be determined.…”
Section: Discussion Prdm12 Function In Vertebrate V1 In Specificationmentioning
confidence: 99%
“…Prdm12 is highly conserved during evolution (Nagy et al, 2015), and we identified orthologous sequences in the chicken and the cephalochordate amphioxus (Branchiostoma lanceolatum), a basal chordate (supplementary material Fig. S1).…”
Section: Cloning and Expression Of Xenopus Chicken And Amphioxus Prdmentioning
confidence: 99%
See 1 more Smart Citation
“…Ген PRDM12 кодирует эпигенетический регулятор, который является ключевым в процессе мейоза, участвует в нейрогенезе и влияет на свойства нервных клеток [18,24]. PRDM12 необходим для разви-тия сенсорного нейрона и восприятия боли [17,[25][26][27]. Было показано участие гена PRDM12 в модуляции ноцицепторов и сенсорных нейронов у эмбрионов Xenopus [17].…”
unclassified